2021
DOI: 10.1371/journal.pone.0248371
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of SARS-CoV-2 reveals the detection of G614 variant in Pakistan

Abstract: Since its emergence in China, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide including Pakistan. During the pandemic, whole genome sequencing has played an important role in understanding the evolution and genomic diversity of SARS-CoV-2. Although an unprecedented number of SARS-CoV-2 full genomes have been submitted in GISAID and NCBI, data from Pakistan is scarce. We report the sequencing, genomic characterization, and phylogenetic analysis of five SARS-CoV-2 strains isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
0
43
0
2
Order By: Relevance
“…We show that in Karachi there was a shift from S, L, V and G clades in March to predominantly the GH clade strains from May onwards [ 17 ]. Traveler- associated strains belonged to S and GH clades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that in Karachi there was a shift from S, L, V and G clades in March to predominantly the GH clade strains from May onwards [ 17 ]. Traveler- associated strains belonged to S and GH clades.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic was initially associated with travelers but local transmission was identified within two weeks of the first known COVID-19. G and S clade strains were shown to be present in the first wave of COVID-19 in Pakistan [ 17 ]. Genetic studies of SARS-CoV-2 from the second wave in Pakistan have identified B.1 and its sub-clades together with B.6 lineage strains to be present [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These mutations may increase transmissibility, enhance escape from the human immune response, or otherwise alter biologically important phenotypes [6]. The global emergence of several variants of concern (VOCs), recently re-named by WHO, including the UK variant (Alpha or B.1.1.7), the South Africa variant (Beta or B.1.351), Brazil variant (Gamma or P.1 and P.2), and Delta or B.1.617.2 variant in India lead the genomic surveillance essential to monitoring mutations [7]. We hereby report the complete genome sequences and phylogenetic analysis of 24 SARS-CoV-2 genomes from Tocantins, North region of Brazil including our P.1-related sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Health authorities need to ramp up genetic sequencing to map any new variants of the virus to tailor the response accordingly. 2 In addition to these measures, the health authorities also need to focus on risk communication and community engagement to deal with the misconceptions regarding COVID-19. Pakistan is lagging behind the neighbouring countries in the vaccination drive and merely relying on international aid for vaccination will not serve the purpose.…”
mentioning
confidence: 99%